Detection of Vitamin C in Samples of Some Crops in Zliten City - Kondi, Boshra Mohammed; Kondi, Huda Mohammed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This research was concerned with collecting the fruits of plant crops from the Wadi Majer and Azdo regions in the city of Zliten. The infusion of these fruits and the aqueous extracts were prepared according to previous references and research. This research aims to detect the presence of vitamin C in the fruits of the plant samples selected for this study, which are lemon, pomegranate, pear, grape, date, sweet pepper, hot pepper and tomato. It was found that ascorbic acid was present in all plant samples except dates. The stability of vitamin C was also studied under storage conditions at room temperature and refrigerator temperature, and it was found that this vitamin has poor stability under storage conditions.
Keywords: Vitamin C; Fruits; Stability; Zliten; Plant extracts; Crops